Renewed calls for abortion-related research in the post-Roe era - Schott, Sophie L.; Adams, April; Dougherty, Ryan J.; Montgomery, Taylor; Lapite, Folasade C.; Fletcher, Faith E. (Frontiers in Public Health, 2023)
Nearly 50 years after Roe versus Wade, the United States Supreme Court’s decision in Dobbs versus Jackson Women’s Health Organization unraveled the constitutional right to abortion, allowing individual states to severely restrict or ban the procedure. In response, leading medical, public health, and community organizations have renewed calls for research to elucidate and address the burgeoning social and medical consequences of new abortion restrictions. Abortion research not only includes studies that establish the safety, quality, and efficacy of evidence-based abortion care protocols, but also encompasses studies on the availability of abortion care, the consequences of being denied an abortion, and the legal and social burdens surrounding abortion. The urgency of these calls for new evidence underscores the importance of ensuring that research in this area is conducted in an ethical and respectful manner, cognizant of the social, political, and structural conditions that shape reproductive health inequities and impact each stage of research—from protocol design to dissemination of findings. Research ethics relates to the moral principles undergirding the design and execution of research projects, and concerns itself with the technicalities of ethical questions related to the research process, such as informed consent, power relations, and confidentiality. Critical insights and reflections from reproductive justice, community engagement, and applied ethics frameworks have bolstered existing research ethics scholarship and discourse by underscoring the importance of meaningful engagement with community stakeholders—bringing attention to overlapping structures of oppression, including racism, sexism, and ways that these structures are perpetuated in the research process.